CONIELECOMP 2012, 22nd International Conference on Electrical Communications and Computers 2012
DOI: 10.1109/conielecomp.2012.6189880
|View full text |Cite
|
Sign up to set email alerts
|

The effects of blood glucose changes on frequency-domain measures of HRV signal in type 1 diabetes

Abstract: The analysis of time duration between consecutive R waves of electrocardiogram (ECG) is a standard method to evaluate the variations in heart rate. The physiological literature reveals that blood glucose levels modulate the autonomic nervous system (ANS) activity and heart rate variability (HRV) is representative of the cardiovascular autonomic function. In the research described here, a pilot investigation was carried out to investigate the relationship between HRV signal measures derived from ECG and arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…Mean RR and LF/HF ratio were also reduced but did not achieve statistical significance. This result concurs with other reports that described lower HRV measures in diabetic patients than in normal subjects [3,12,17]. Table II demonstrated that BGLs were inversely and significantly correlated with SDNN, RMSSD, pNN50 and LF and HF (p<0.05).…”
Section: A Heart Rate Variabilitysupporting
confidence: 82%
See 1 more Smart Citation
“…Mean RR and LF/HF ratio were also reduced but did not achieve statistical significance. This result concurs with other reports that described lower HRV measures in diabetic patients than in normal subjects [3,12,17]. Table II demonstrated that BGLs were inversely and significantly correlated with SDNN, RMSSD, pNN50 and LF and HF (p<0.05).…”
Section: A Heart Rate Variabilitysupporting
confidence: 82%
“…The power of LF, HF and VLF components is usually expressed in absolute units (ms 2 ). The ratio between LF and HF components (LF/HF ratio) is used to reflect the balance between sympathetic and parasympathetic parts of the autonomic system and hence shows the level of sympathetic dominance (stress) in a subject [17]. These time and frequency domains parameters are considered to be most physiologically linked to the autonomic nervous system.…”
Section: B Variability Assessmentmentioning
confidence: 99%
“…Other works have shown that blood heart rate variability (HRV) can be modulated by blood glucose levels [ 27 ]; therefore, several studies investigating HRV and glucose levels have been developed. Amanipour et al [ 27 ] analyzed the HRV frequency domain components of a 59-year old diabetic female subject under normoglycemic and hyperglycemic conditions. They noticed a 6-fold decrease in the low frequency/high frequency ratio.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ratio of low frequency component to that of the high frequency component decreased when the blood glucose levels are changed from normoglycaemic to hypoglycaemic condition. This pilot study brought out only the brief relationship between the HRV spectral parameters and sugar levels during normoglycaemic and mildly hyperglycaemic conditions (Amanipour et al, 2012). In another study, the HRV in healthy individuals and diabetic patients is compared to find that a negative correlation exists between HbA1c values and the HRV parameters (Mirza and Laxmi, 2012).…”
Section: Introductionmentioning
confidence: 99%